A modality of distance education from its planning, learning curriculum and assessment / A modalidade de educação a distância a partir de seu planejamento, currículo e avaliação da aprendizagem - Ailson Darlan Sales Ferreira; Adelma Talline Silva; Any Raphaely Soares de Melo; Karol Fireman de Farias; Luciara Cavalcante Lima; Rubens Pereira Bezerra (Universidade Estadual de Alagoas, 2016)
In order to provide the reader a remarkable presentation of Education teaching mode Distance (EAD), from its inception to its recognition as a method for the main law has as objective to expose the conceptual bases underlying the planning of ODL, the authors sought to discuss the curriculum of it, from reading articles and dialogues with students and teachers of this modality, and with a brief discussion of the same for the face modality. Intending to an assistance means for already active teachers in education, the sport has emerged as an alternative means for those seeking a second training so that they can meet the demands of the profession especially in the interior regions, which are increasingly precarious qualified professionals. However, the EAD also does not fail to affect areas of Bachelor, meeting the needs of those who work and seek an academic background. It may be noted that as a means of imparting education and form citizen, distance education suffers from problems as any other means of education. But, in short, the mode comes as an alternative means of encouragement for students who do not have the same availability times a classroom teaching student. Note that DL came not to exterminate the classroom teaching model, but to meet the needs in which this was not realizing.